2019
DOI: 10.1007/s10111-019-00549-4
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the concept of simulator fidelity: the use of technology and collaborative activities in training maritime officers

Abstract: The theoretical contribution of this paper lies in introducing the concept of social fidelity to bridge the gap between computer technology and collaborative learning activities in simulator-based training. The concept has usually been limited to the technological aspects of simulator training with an assumption that a high level of fidelity equals a high physical resemblance between a simulator and the real work environment. The objective of this article is to expand the prevailing understanding of the concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In addition to the physical, functional, behavioral, and perceptual (psychological) fidelity, researchers have also added another dimension i.e., social fidelity, into the discussion. The term “social fidelity” refers to the nature of social interactions as a part of collaborative activities that are embedded into the simulation scenario (Wahl 2020 ). Hontvedt and Øvergård ( 2020 ) used the term “interactional fidelity” to refer to the simulation of team coordination and collaboration in socio-technical environments.…”
Section: The Use Of Simulators In Maritime Education and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the physical, functional, behavioral, and perceptual (psychological) fidelity, researchers have also added another dimension i.e., social fidelity, into the discussion. The term “social fidelity” refers to the nature of social interactions as a part of collaborative activities that are embedded into the simulation scenario (Wahl 2020 ). Hontvedt and Øvergård ( 2020 ) used the term “interactional fidelity” to refer to the simulation of team coordination and collaboration in socio-technical environments.…”
Section: The Use Of Simulators In Maritime Education and Trainingmentioning
confidence: 99%
“…The learning occurs through the active role played by the trainees in the simulation session and supported by the instructors in orienting the trainees and scaffolding throughout the process. Similarly, Wahl ( 2020 ) demonstrated that the learning occurring in the maritime simulation-based training and education is not solely influenced by the physical and psychological fidelity. She commented on the importance of social fidelity i.e., the extent to which the trainee-instructor interactions in the simulator and the joint collaboration activities exercised as if in the actual work environment.…”
Section: Simulator-based Met In the Post Covid-19 Eramentioning
confidence: 99%
“…For example, the warship's commanding officer is responsible for leading the bridge team (in some navigation conditions) and the operations room team, contributing to safety and efficient ship operation (Wahl, 2019). Working with these teams, in highly dynamic conditions, implies that the commanding officer, in order to achieve a safe and efficient level of teamwork (Wahl, 2019), must develop incident command skills (Arbuthnot, 2017), grounded on NTS which in turn are developed through BRM training. It is through development of these skills that the commanding officer can better achieve the necessary command and control essential for the authority and direction of the assigned forces (DoD, 2008).…”
Section: Bridge Resource Management and The Minimisation Of Human Errormentioning
confidence: 99%
“…The activity model used in this study is based on Engeström's (1987) model of activity systems, expanded from the work by Vygotsky (1986) and Leont'ev (1978). Engeström's model (see Fig.…”
Section: Theoretical and Analytical Framework: Activity Theorymentioning
confidence: 99%